XPS STUDIES ON THE ELECTRONIC STRUCTURE OF BONDING BETWEEN SOLID AND SOLUTES: ADSORPTION OF ARSENATE, CHROMATE, PHOSPHATE, PB2+, AND ZN2+ IONS ON AMORPHOUS BLACK FERRIC OXYHYDROXIDE - Ding M.; de Jong B.H.W.S.; Roosendaal S.J.; Vredenberg A. (My University, 2000)
The adsorption of three anions (AsO43-, PO43-, and CrO42-) and two cations (Zn2+ and Pb2+) has been determined on a new form of amorphous black ferric oxyhydroxide that resembles in local structure β-FeOOH, akaganeite. The nature of the interaction between FeOOH substrate and the above mentioned adsorbates is characterised with X-ray photoelectron spectroscopy on the core and valence band levels of trivalent iron and oxygen using frontier molecular orbital theory as theoretical framework. Our findings indicate that substantial and variable charge transfer occurs in which the FeOOH substrate can function either as a Lewis acid or base in its interaction with different adsorbates. Our findings suggest that the valence band spectra can be used to estimate qualitatively the energy level separation between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of the surface complexes and to assess the chemical affinity between substrate and adsorbate.